2009
DOI: 10.1177/0961203308098598
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve prolapse in young healthy individuals. An early index of autoimmunity?

Abstract: Mitral valve prolapse (MVP) is a benign valvular abnormality. However, an increased prevalence of MVP is reported in patients with systemic lupus erythematosus and autoimmune thyroid disease. Our aim was to evaluate whether the presence of MVP in healthy individuals might indicate a premature index of subclinical autoimmune disorder. A total of 75 individuals with MVP and 44 individuals without MVP were identified by echocardiography. Serum samples were examined for various organ and non-organ specific autoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…These high rates may be due to differences in the patient selection. Unlike in our study, some patients in other studies in the literature were found to be euthyroid, subclinical, and with no signs of Hashimoto's thyroiditis in the ultrasonography (7,8,16,17). Another difference between the ratios originated from patient population of the study.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…These high rates may be due to differences in the patient selection. Unlike in our study, some patients in other studies in the literature were found to be euthyroid, subclinical, and with no signs of Hashimoto's thyroiditis in the ultrasonography (7,8,16,17). Another difference between the ratios originated from patient population of the study.…”
Section: Discussioncontrasting
confidence: 82%
“…Apart from hereditary connective tissue diseases, it was mostly related to autoimmune thyroid disease excluding. It was reported that MVP was frequent in both Graves' disease and Hashimoto's disease, and other markers of autoimmunity were also found to be increased in patients with MVP in addition to autoimmune thyroid disease (7,8,(14)(15)(16). Evangelopoulous et al reported in 1999 that they diagnosed MVP in eight out of 29 (28%) adult patients with Graves' disease, and in eight out of 35 (23%) patients with Hashimoto's thyroiditis, but there was no MVP in the control group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, they concluded that patients with MVP may have a higher autoimmune disease incidence because both diseases have similar family characteristics and are associated with tissue antigens, including HLA-D3, BW35, and A3. In another study by Evangelopoulos et al (20), the immunological parameters were investigated in patients with autoimmune thyroid diseases, and the association between MVP and autoimmune diseases (22). In 29 patients with Graves' disease, nine had MVP, whereas none of the controls had MVP (p<0.05).…”
Section: Discussionmentioning
confidence: 99%